Freeing Mysticism: Epistemic Standards in Theory and Practice - Cooney, John (Stance: an international undergraduate philosophy journal, 2019)
With the growth of epistemology, an important debate in philosophy of religion has arisen: can mystical encounters—purported feelings of intense unity with the divine—serve as epistemic warrants? In this paper, I examine two of the most prominent and promising standards by which to determine the veridicality of such encounters—those of William Alston and Richard Swinburne—and demonstrate their respective strengths and shortcomings. Considering these shortcomings, I compose and defend my own set of criteria to use in evaluating the veridicality of putative mystical experiences which draws upon the subject’s religious tradition, rationality, and affectivity.